The Azores: A Mid-Atlantic Hotspot for Marine Megafauna Research and Conservation - Afonso, Pedro; Fontes, Jorge; Giacomello, Eva; Magalhães, Maria C.; Martins, Helen R.; Morato, Telmo; Neves, Verónica; Prieto, Rui; Santos, Ricardo S.; Silva, Mónica A.; Vandeperre, Frédèric (Frontiers in Marine Science, 2020)
The increasing public perception that marine megafauna is under threat is an outstanding incentive to investigate their essential habitats (EMH), their responses to human and climate change pressures, and to better understand their largely unexplained behaviors and physiology. Yet, this poses serious challenges such as the elusiveness and remoteness of marine megafauna, the growing scrutiny and legal impositions on their study, and difficulties in disentangling environmental drivers from human disturbance. We argue that advancing our knowledge and conservation on marine megafauna can and should be capitalized in regions where exceptional access to multiple species (i.e. megafauna ‘hotspots’) combines with the adequate legal framework, sustainable practices, and research capacity. The wider Azores region, hosting EMHs of all key groups of vulnerable or endangered vertebrate marine megafauna, is a singular EMH hotspot on a migratory crossroads, linking eastern and western Atlantic margins and productive boreal waters to tropical seas. It benefits from a sustainable development model based on artisanal fisheries with zero or minor megafauna bycatch, and one of the largest marine protected area networks in the Atlantic covering coastal, oceanic and deepsea habitats. Developing this model can largely ensure the future integrity of this EMH hotspot while fostering cutting-edge science and technological development on megafauna behavior, biologging and increased ocean observation, with potential major impacts on the Blue Growth agenda. An action plan is proposed.